Low appendicular skeletal muscle mass (ASM) with limited mobility and poor health outcomes in middle‐aged African Americans. Issue 3 (27th March 2013) - Malmstrom, Theodore K.; Miller, Douglas K.; Herning, Margaret M.; Morley, John E.
Abstract : Background: Recent efforts to provide a consensus definition propose that sarcopenia be considered a clinical syndrome associated with the loss of both skeletal muscle mass and muscle function that occurs with aging. Validation of sarcopenia definitions that include both low muscle mass and poor muscle function is needed. Methods: In the population‐based African American Health (AAH) study ( N = 998 at baseline/wave 1), muscle mass and mobility were evaluated in a clinical testing center in a subsample of N = 319 persons (ages 52–68) at wave 4 (2004). Muscle mass was measured using dual energy x‐ray absorptiometry and mobility by a 6‐min walk test and 4‐m gait walk test. Height corrected appendicular skeletal mass (ASM; 9.0 ± 1.5 in n = 124 males, 8.3 ± 2.2 in n = 195 females) was computed as total lean muscle mass in arms and legs (kilograms) divided by the square of height (meters). Cross‐sectional and longitudinal (6‐year) associations of low ASM (bottom 25 % AAH sample; <7.96 males and <7.06 females) and low ASM with limited mobility (4‐m gait walk ≤1 m/s or 6‐min walk <400 m) were examined for basic activities of daily living (ADL) difficulties, instrumental activities of daily living (IADL) difficulties, frailty, falls, and mortality (longitudinal only). Results: Low ASM with limited mobility was associated with IADL difficulties ( p = .008) and frailty ( p = .040) but not with ADL difficulties or falls in cross‐sectional analyses; and with ADL difficulties ( p = .022), IADL difficulties ( p = .006), frailty ( p = .039), and mortality ( p = .003) but not with falls in longitudinal analyses adjusted for age and gender. Low ASM alone was marginally associated with mortality ( p = .085) but not with other outcomes in cross‐sectional or longitudinal analyses. Conclusion: Low ASM with limited mobility is associated with poor health outcomes among late middle‐aged African Americans.